'Low‐hanging fruit' for conservation of marine vertebrate species at risk in the Mediterranean Sea. Issue 2 (4th November 2014) - Coll, Marta; Steenbeek, Jeroen; Ben Rais Lasram, Frida; Mouillot, David; Cury, Philippe
Abstract Aim Conservation priorities need to take the feasibility of protection measures into account. In times of economic pressure it is essential to identify the 'low‐hanging fruit' for conservation: areas where human impacts are lower and biological diversity is still high, and thus conservation is more feasible. Location We used the Mediterranean large marine ecosystem (LME) as a case study to identify the overlapping areas of low threats and high diversity of vertebrate species at risk. Methods This LME is the first in the world to have a complete regional IUCN Red List assessment of the native marine fish. We augmented these data with distributions of marine mammals, marine turtles and seabirds at risk, and we calculated the spatial distributions of species at risk (IUCN densities). Using cumulative threats we identified 'priority areas for conservation of species at risk' (PACS), where IUCN diversities are high and threats are low. We assessed whether IUCN diversities and PACS were spatially congruent among taxa and we quantified whether PACS corresponded to current and proposed protected areas. Results IUCN densities and PACS were not highly correlated spatially among taxa. Continental shelves and deep‐sea slopes of the Alboran Sea, western Mediterranean and Tunisian Plateau/Gulf of Sidra are identified as relevant for fish species at risk. The eastern side of the western Mediterranean and the Adriatic Sea are identified as most relevant for endemic fish, and shelf and open sea areas distributed through the LME are most important for marine mammals and turtles at risk, while specific locations of the western Mediterranean Sea and the Aegean and Levantine seas are highlighted for seabirds. Main conclusions Large parts of the areas of PACS fell outside current or proposed frameworks to be prioritized for conservation. PACS may be suitable candidates for contributing to the 10% protection target for the Mediterranean Sea by 2020.